Mathematical and Computer Models For Thermodynamic Properties of Methane R-50, Ethylene R-1150, and Propylene R- 1270 - Mohammed K. Mohammed; Nassir D. Mokhlif (Tikrit Journal of Engineering Sciences, 2006)
A set of computer methods for calculating densities, vapor pressures, enthalpies, internal energies and entropies of methane (R-50), ethylene (R-1150), and propylene (R-1270) to be described. Formulation and solution of equations for these thermodynamic properties to be presented first based on what published by ASHRAE. The data obtained from these subroutines showed very small and acceptable percentage errors when compared with ASHRAE data and what available in the literature. These results ensure that these subroutines are acceptable.